PROSEDUR PEMBERIAN IZIN PENGELOLAAN PASAR RAKYAT DI KOTA PEKANBARU - Noviani Rosa Irene Purba; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The market is one of the factors supporting the economy of the people in Pekanbaru. The market presence in the city of Pekanbaru is quite a lot. Market managers are also not only from the government, but also private and third parties. The procedure for obtaining community market management permits is still a difficult thing to do with regard to the large number of people's markets in Pekanbaru City that do not have a formal and clear management permit. Most of the markets that have not yet beeb licensed have been established before the regulation was made. This is due to the procedure for obtaining long permits and taking a long time. Regarding this licensing has been regulation in Perda Number 9 of 2014 The purpose of this study was to find out the implementation of the procedure for granting community market management licenses in the city of Pekanbaru and to find out the inhibiting factors for the procedure for granting such permits. The theory used in this study is the theory of George Edwards III which has 4 factors that support the success of implementation, namely communication, resources (resources), disposition and bureaucratic structure (SOP). The method used is a type of qualitative research with data collection techniques using purposive sampling technique. The results of this study indicate that there is an inhibiting factor in obtaining permits according to the procedure, namely the length of the procedure for obtaining permits in the Disperindag and the lack of socialization from DPMPTSP and the Disperindag in informing this procedure. Keywords: Market, Procedure, Permit, Implementation